Murine colon organoids as a novel model to study Trypanosoma cruzi infection and interactions with the intestinal epithelium - Daghero, Hellen; Pagotto, Romina; Quiroga, Cristina; Medeiros, Andrea; Comini, Marcelo A.; Bollati-Fogolín, Mariela (Frontiers in Cellular and Infection Microbiology, 2023)
Chagas disease (CD) is a life-threatening illness caused by the parasite Trypanosoma cruzi (T. cruzi). With around seven million people infected and over 50,000 deaths annually, CD is a major public health issue in Latin America. The main route of transmission to humans is through a triatomine bug (vector-borne) but congenital and oral transmission have also been reported. The acute phase of CD presents mild symptoms but may develop into a long-lasting chronic illness, characterized by severely impaired cardiac, digestive, and neurological functions. The intestinal tissue appears to have a key role during oral transmission and chronic infection of CD. In this immune-privileged reservoir, dormant/quiescent parasites have been suggested to contribute to disease persistence, infection relapse, and treatment failure. However, the interaction between the intestinal epithelium and T. cruzi has not been examined thoroughly, in part, due to the lack of suitable in vitro models of this organ. Therefore, to understand the role of the intestinal epithelia during transmission and chronic infection, we established colon stem cell-derived organoid infection models. Murine organoids infected with T. cruzi Dm28c were analyzed by confocal microscopy. T. cruzi was able to invade and replicate in colon cells grown as intact organoids (3D) and monolayers (2D). The permissiveness to pathogen infection differed markedly between organoids and cell lines (primate and intestinal human cell lines). So far, this represents the first evidence of the potential that these cellular systems offer for the study of host-pathogen interaction and the discovery of effective anti-chagasic drugs.